OPPRESSION ON WOMAN AS REFLECTED IN LAKSHMI’S CHARACTER OF SOLD NOVEL BY PATRICIA MCCORMICK - Kristami, Oktarny; Surya, Satyawati; Lubis, Indah Sari (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2022)
In this research, the researcher shows the forms of oppression which occur toward female character named Lakshmi. The five faces of oppression is a theory that is explained by Irish Marion Young. The kinds of oppression toward women can be found in Lakshmi’s character of Sold novel. This form of oppression somehow called as injustice action that adhere toward people or group because of several reasons, such as class, race and gender. The source of data of this study are collected from Patricia McCormick’s Sold novel and the data for this study is the evidence of oppression toward Lakshmi. The oppression is divided into exploitation, marginalization, powerlessness, cultural imperialism and violence. The results of this study are, Lakshmi got five faces oppression from group or person. Based on that analysis, the researcher concludes that the oppression toward women can be done by men also women. Therefore, the researcher believes that the oppression toward women is not happens because of gender that men is superior rather than women, but oppression can be happened due to power of domination and class.